2018
DOI: 10.21873/invivo.11364
|View full text |Cite
|
Sign up to set email alerts
|

T790M Correlates with Longer Progression-free Survival in Non-small Cell Lung Carcinomas HarboringEGFRMutations

Abstract: It is highly recommended that patients with exon 19 deletions and long PFS undergo screening for T790M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…The exclusion of a number of prolonged EGFR -TKI responders who had not experienced PD in the present study could be a confounding factor because previous studies suggested these patients are more likely to acquire T790M mutation at PD. 18 , 19 , 21 - 23 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exclusion of a number of prolonged EGFR -TKI responders who had not experienced PD in the present study could be a confounding factor because previous studies suggested these patients are more likely to acquire T790M mutation at PD. 18 , 19 , 21 - 23 …”
Section: Discussionmentioning
confidence: 99%
“…26 Otherwise, the present study and other studies consistently observe that gender, smoking status, proportion of stage IV disease and the site of re-biopsy do not have a significant effect on the frequency of acquired T790M mutation. 21 , 23 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conclusion: The diagnostic performance of PANAMutyper™ was superior to that of PNAClamp™ for the detection of EGFR mutations. It was also better at identifying lung cancer patients with malignant pleural effusion who were likely to benefit from EGFR-TKI treatment.The use of molecular agents targeting the epidermal growth factor receptor (EGFR) is important in the treatment of advanced non-small cell lung cancer (NSCLC) (1-3).Multiple prospective clinical trials have demonstrated that patients with advanced NSCLC harboring activating mutations in the EGFR gene show improved objective response rates and progression-free survival (PFS) when treated with EGFR tyrosine kinase inhibitors (EGFR-TKIs) (1,2,(4)(5)(6)(7)(8). Therefore, molecular testing for EGFR mutations has become essential for predicting whether a patient will benefit from EGFR-TKI targeted therapy (9).Previously, we compared peptide nucleic acid (PNA) clamping with direct sequencing for the detection of EGFR and K-RAS mutations.…”
mentioning
confidence: 99%
“…Multiple prospective clinical trials have demonstrated that patients with advanced NSCLC harboring activating mutations in the EGFR gene show improved objective response rates and progression-free survival (PFS) when treated with EGFR tyrosine kinase inhibitors (EGFR-TKIs) (1,2,(4)(5)(6)(7)(8). Therefore, molecular testing for EGFR mutations has become essential for predicting whether a patient will benefit from EGFR-TKI targeted therapy (9).…”
mentioning
confidence: 99%